2020
DOI: 10.3389/fimmu.2020.585502
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Inflammation Confers Protective Immunity Against Liver Stages of Malaria Parasite

Abstract: Deciphering the mechanisms by which Plasmodium parasites develop inside hepatocytes is an important step toward the understanding of malaria pathogenesis. We propose that the nature and the magnitude of the inflammatory response in the liver are key for the establishment of the infection. Here, we used mice deficient in the multidrug resistance-2 gene (Mdr2 −/−)-encoded phospholipid flippase leading to the development of liver inflammation. Infection of Mdr2 −/− mice with Plasmodium berghei ANKA (PbANKA) sporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Our laboratory has gathered during the last decade experimental evidence, using various murine models for malaria, that the IL-6 response is critical in controlling the parasite growth by generating an effective anti-parasite immune response [8, 9, 7, 10]. We decided to focus our study on the IL-6 cytokine for multiple reasons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our laboratory has gathered during the last decade experimental evidence, using various murine models for malaria, that the IL-6 response is critical in controlling the parasite growth by generating an effective anti-parasite immune response [8, 9, 7, 10]. We decided to focus our study on the IL-6 cytokine for multiple reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent work, we used mice deficient in the multidrug resistance-2 gene ( Mdr2 −/− ), which encodes the canalicular phospholipid flippase leading to a complete absence of phospholipids from bile, which were found to spontaneously develop liver injury with a typical inflammatory profile. In this model, we demonstrated that the intra-hepatocyte parasite development was impaired via an IL-6-dependent mechanism [10] and the abortive infection resulted in a long-lasting immunity in Mdr2 −/− mice against infectious SPZ. This IL-6-driven potent immune response was observed in the Mdr 2 −/- mouse model we reported recently where not only total CD8 + and CD4 + cells but also CD8 + and CD4 + tissue resident memory T cells were present at a significantly higher levels in SPZ challenged Mdr2 −/- mice [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During infection of malaria, Plasmodium promotes the development of antigens-specific T RM cells ( 16 , 125 127 ). These T RM cells could mediate protective immune responses through killing infected cells by producing pro-inflammatory cytokines, such as IFN-γ and TNF-α ( 16 , 30 ). Additionally, T RM cell depletion abrogated an efficient immune response to a murine model of Plasmodium infection ( 31 ).Due to the protective immune response of T RM cells against malaria, vaccination strategies that maximize intrahepatic Plasmodium -specific T RM development have emerged ( 16 , 28 , 29 , 32 34 , 127 ).…”
Section: Liver T Rm Cells In the Chronic Liver Dis...mentioning
confidence: 99%